Penerapan Motif Ukiran Minangkabau Sebagai Jam Hias - Febri Darul Islam; Asra IIal Khairi (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
The aim of making this work is to visualize the meaning contained in Minangkabau motifs in carvings using surian wood as a three-dimensional work with the theme being the lessons we take from everyday life. The method used in making this work goes through several stages, namely: (1). Preparation Stages, (2). Elaboration Stages, (3). Synthesis Stages, (4). Concept Realization Stages, (5). Finishing stages The results of the works that have been visualized in two-dimensional media have been developed resulting in the titles kaluak Paki, "bungo panca matoari", "Carano Kanso", "pucuak rabuang", "kambang manih", "Bungo Teratai", "siriah gadang."